Dishing out mini-brains: Current progress and future prospects in brain organoid research - Kelava, Iva (Dev Biol, 2016)
The ability to model human brain development in vitro represents an important step in our study of developmental processes and neurological disorders. Protocols that utilize human embryonic and induced pluripotent stem cells can now generate organoids which faithfully recapitulate, on a cell-biological and gene expression level, the early period of human embryonic and fetal brain development. In combination with novel gene editing tools, such as CRISPR, these methods represent an unprecedented model system in the field of mammalian neural development. In this review, we focus on the similarities of current organoid methods to in vivo brain development, discuss their limitations and potential improvements, and explore the future venues of brain organoid research.